Writing beyond the classroom: Insights on authenticity and motivation - Roberts, Gisel; Banegas, Darío Luis (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The current article aims at arguing that engaging learners with writing tasks whose products are later socialised with a wider community may promote higher motivation and English language proficiency among learners. In this contribution, we discuss recent notions on motivation and authenticity in language learning and analyse writing tasks. Finally, we put forward initiatives and pedagogical implications for transforming writing development into an authentic experience for learners and teachers regardless of their English language proficiency. Although our reflections and examples come from our experience as EFL teachers in Argentina, we believe that our insights and discussions may resonate with other contexts.